2021
DOI: 10.33105/itrev.v6i2.355
|View full text |Cite
|
Sign up to set email alerts
|

Realitas Penatausahaan Piutang Pajak Pemerintah

Abstract: The Audit Board of the Republic of Indonesia (BPK) had findings on tax receivables in the last seven years, indicate that the DGT has not managed tax receivables properly. This study aims to analyze problems in the administration of tax receivables at DGT, benchmarking with other countries, and provide suggestions to solve these problems. This study uses a qualitative method with case studies at the DGT and some other tax authorities as multiple units of analysis. Data collection are carried out through interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The findings of this study showed that there is a strong, positive correlation between an internal audit control and integrity system and good governance. Results from Pratiwi, D and Martani, D [13] research corroborate this; indicating that both an internal control system and integrity system have a significant positive impact on good governance, while the integrity system also moderates the relationship between internal control and good governance. The authors suggest ways in which local governments can reinforce their internal control and integrity systems, implying that these findings are highly valuable when it comes to improving governance in local government.…”
Section: Results and Findingsmentioning
confidence: 75%
“…The findings of this study showed that there is a strong, positive correlation between an internal audit control and integrity system and good governance. Results from Pratiwi, D and Martani, D [13] research corroborate this; indicating that both an internal control system and integrity system have a significant positive impact on good governance, while the integrity system also moderates the relationship between internal control and good governance. The authors suggest ways in which local governments can reinforce their internal control and integrity systems, implying that these findings are highly valuable when it comes to improving governance in local government.…”
Section: Results and Findingsmentioning
confidence: 75%